Changing Focuses Through the Progression of Hungarian Water Management (Academic Journal of Internal Affairs, 2021)
Hungary is one of the best examples to represent the manifestation of hydrological extremes. Studying the history of Hungarian water management and examining our present show how water management has developed. As time passes, changing job scopes and the expansion of available tools are recognisable. During the development, water management experts have been heading from ad hoc interventions to coordinated complex planning and in the meanwhile the process shows in which direction the focus points have changed. The aim of this paper is to explore the way Hungarian water management is heading under the changing circumstances. It examines the place and role of Hungary in the development of water management. The author researches the correctness of the direction of development and the change of focus points in comparison with other countries. Building on past experiences, this paper seeks the answer for the question how water management will be in the future. Research results provide guidance on how Hungarian water management can be at the forefront of future modern water management.
Keywords: water management; engineering; development; history